MiRNAexpression profile of retinal pigment epithelial cells under oxidative stress conditions. Issue 2 (2nd January 2018) - Donato, Luigi; Bramanti, Placido; Scimone, Concetta; Rinaldi, Carmela; D'Angelo, Rosalia; Sidoti, Antonina
Abstract : Deep analysis of regulative mechanisms of transcription and translation in eukaryotes could improve knowledge of many genetic pathologies such as retinitis pigmentosa (RP). New layers of complexity have recently emerged with the discovery that 'junk' DNA is transcribed and, among these, miRNAs have assumed a preponderant role. We compared changes in the expression of miRNAs obtained from whole transcriptome analyses, between two groups of retinal pigment epithelium (RPE) cells, one untreated and the other exposed to the oxidant agent oxidized low‐density lipoprotein (oxLDL), examining four time points (1, 2, 4 and 6 h). We found that 23 miRNAs exhibited altered expression in the treated samples, targeting genes involved in several biochemical pathways, many of them associated to RP for the first time, such as those mediated by insulin receptor signaling and son of sevenless. Moreover, five RP causative genes ( KLHL7, RDH11, CERKL, AIPL1 and USH1G ) emerged as already validated targets of five altered miRNAs (hsa‐miR‐1307, hsa‐miR‐3064, hsa‐miR‐4709, hsa‐miR‐3615 and hsa‐miR‐637), suggesting a tight connection between induced oxidative stress and RP development and progression. This miRNA expression analysis of oxidative stress‐induced RPE cells has discovered new regulative functions of miRNAs in RP that should lead to the discovery of new ways to regulate the etiopathogenesis of RP. Abstract : The involvement of miRNAs in the etiopathogenesis of retinitis pigmentosa (RP) was recently reported. Using RNA‐Seq, we compared miRNA expression in retinal pigment epithelium cells exposed to oxidized low‐density lipoprotein with untreated control cells. Treated cells showed 23 dysregulated miRNAs, targeting 1402 genes involved in 822 biochemical pathways, many of them associated for the first time with RP.